A plant product modified carbon black as a reinforcing filler for rubber - Ghosh A K; Adhikari B; Maiti S (Journal of polymer materials, 1995)
A plant product containing long chain substituted phenol (PP) has been used to modify carbon black in the present investigation with an objective to put PP as a flexible bridge between carbon black particles and the polymer to improve its reinforcement behaviour in rubber vulcanizate. Carbon black was treated with PP in presence or absence of aldehyde-ammonia (AA) and free radical donor (FR) separately as a method of modification. Such modified carbon blacks were characterized by gravimetric analysis of extracted samples, ESCA and DPPH reaction followed by evaluation of its bound rubber formation, processing behavior, reinforcement characteristics such as modulus, tensile strength, hardness etc., flex crack growth resistance, abrasion resistance and heat build-up properties in styrene butadiene rubber. The reported results show some positive aspects of reinforcement by the PP modified carbon black.
Keywords: Abrasion loss; Bound rubber; Carbon black modification; Flex cracking; Heat build-up